Elektroniczne przestrzenie widzenia - Gwóźdź, Andrzej (Er(r)go. Teoria - Literatura - Kultura, 2002)
Andrzej Gwóźdź "Electronic Spaces of Seeing" The author of the essay reiterates the questions posed by Merleau-Potty about the subject of seeing, the activity of seeing and the object or the world which is visible. He pays particular attention to the formula video ergo cogito, which appears to be an affirmation of reflection qua metaobservation: since, as radical constructionists insist, we cannot get to to know, and subsequently describe, what we see „from outside", all we can do is focus on how we observe and thus we ascend to a metalevel of observation although we still remain within the world we observe. Furthermore the author of the essay explores the consequences of our reliance on electronic devices which create teleoptic spaces of seeing/being seen. In the typology he introduces the space of seeing comprises the spaces of cognition, representation, monitoring, ritual, transaction, activity and memory.